CONTRIBUTION OF ARM MUSCLE STRENGTH AND BACK FLEXIBILITY TO THE ABILITY OF KAYANG IN FLOOR GYMNASTICS OF MA IBADURRAHMAN MUTTAHIDAH STUDENTS - Nur Afni Aprilia; Maria Her Linda Dos Santos; Khalid Rijaluddin; Nopri Jumadil Ashar (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2025)
Contribution of Arm Muscle Strength and Back Flexibility to the Kayang Ability in Floor Gymnastics of MA Ibadurrahman Muttahidah Students. This study aims to determine the contribution of arm muscle strength and back flexibility to the kayang ability in floor gymnastics of MA Ibadurrahman Muttahidah students. This study is a quantitative study using a regression technique. The population is grade X and XI students of MA Ibadurrahman Muttahidah, and the sample used is 15 people with all male students. The data analysis technique used is the Regression Test (R). The results of the data analysis are as follows: (1). There is a contribution of arm muscle strength to the kayang ability in floor gymnastics, where the R value is obtained = 0.137 with sig. 0.003 < 0.05 (2). There is a contribution of back flexibility to the kayang ability in floor gymnastics, where the R value is obtained = 0.218 with sig. 0.002 < 0.05 (3). There is a contribution of arm muscle strength and back flexibility to the ability to do a bridge in floor gymnastics, where the value of R^2 = 0.781 is obtained with sig. 0.003 <0.05. The conclusion of this study shows that there is a contribution between arm muscle strength and back flexibility to the ability to do a bridge of MA Ibadurrahman Muttahidah students.